(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Mxenes, as a new group of two-dimensional materials in form of transition metal carbides, carbonitrides and/or nitrides, have been playing an important role in the wearable smart electronic field. Due to their abundance surface functional groups, Mxenes have showed their superior dispersions in various solvents which is beneficial to simply the fabrication process of textile-based electronics while their electrical performance guaranteed. In this work, we report a novel fine silk yarn dip-coated in an aqueous solution of Ti_3C_2T_x MXene to obtain low electrical resistance (∼25.6 Ohms/cm). Yarns structures and morphologies were observed by transmission and scanning electron microscopy (TEM & SEM) together with energy dispersive spectroscopy (EDS). Besides, Fourier transform infrared (FTIR) and Raman spectroscopy, and X-ray diffraction (XRD) analysis were carried out to reveal the chemical compositions. By controlling two coating parameters as design of experiments (DoE) factors, we found both solution concentration and soaking time had significant effects on yarn performances. The mechanical performance of yarn fabricated under the optimised coating condition was evaluated by means of tensile testing, resulting in a significant 23% increase in breaking strength (∼107 MPa). In responding to tensile deformation, the dip-coated yarn also performed a linear variation in resistance, which indicated its capability in sensing applications.